Genome-wide association studies and genomic selection for leaf-related traits in maize - Yang, Xinyu; Wu, Penghao; Cui, Wentao; Alimu, Dilinigeer; Wang, Kaixiang; Ren, Jiaojiao (Frontiers in Plant Science, 2025)
Leaf morphological characteristics are critical factors affecting plant architecture and canopy photosynthesis, all of which ultimately affect grain yield. Elucidation of the genetic basis of maize leaf-related traits could assist breeders in designing effective breeding strategies. Genomic selection (GS) is an effective method to accelerate the breeding process. We performed a genome-wide association study (GWAS) and GS for leaf-related traits in a natural maize population consisting of 291 inbred lines. The GWAS panel was phenotyped at four environments for the leaf length of the first leaf above the upmost ear (L1), the upmost ear leaf (L2), the first leaf below the upmost ear (L3), leaf width of L1, L2, and L3, leaf area of L2 (LAr2), and leaf number above the upmost ear (LNAE), and genotyped by sequencing. The heritability of leaf-related traits was ranged from 77.93% to 87.54%. A total of 24 unique significant SNPs were identified for leaf length at the p-value threshold of 2.968 × 10–6 by FarmCPU and BLINK models. The phenotypic variation explained (PVE) by each SNP ranged from 4.82% to 20.7%. A total of 34 unique significant SNPs were identified for leaf width, each with a PVE ranging from 0.01% to 17.2%. A total of 14 unique significant SNPs were identified for LAr2, each with a PVE ranging from 0.7% to 21.8%. A total of 19 unique significant SNPs were identified for LNAE, each with a PVE ranging from 1.21% to 25.01%. Eleven pleiotropic SNPs controlling leaf-related traits were identified, indicating that the leaf length and width at different leaf positions may be influenced by one or more common loci. A total of 122 candidate genes were retrieved, among which Zm00001eb297330, Zm00001eb275550, Zm00001eb377180, Zm00001eb296310, and Zm00001eb178140 are key candidate genes for leaf-related traits. The results of GS indicated that a training population size of 70% and a set of 3000 SNPs were adequate for the application of GS in maize leaf-related traits. This study provides important reference information for further elucidating the genetic basis of leaf-related traits and applying GS in maize breeding programs.